PERTANGGUNGJAWABAN PIDANA BAGI ANAK YANG MELAKUKAN KEKERASAN FISIK TERHADAP PEMBANTU RUMAH TANGGA (Analisis Putusan Nomor: 27/Pid.Sus-Anak/2014/PN.MDN) - Atikah Rahmi; Suci Putri Lubis (Universitas Muhammadiyah Sumatera Utara, 2017)
The imposition of criminal sanctions on children effects bad mental for development of children. Medan District Court has given criminal sanctions to children through Decision Number: 27/Pid.Sus-Anak/2014/Pn.Mdn. This verdict becomes interesting object to examine in aiming to know the criminal liability imposed on the child by analyzing the decision. This research is a normative juridical research with case approach, while its characteristic is descriptive. Data analysis is done by qualitative juridical. Based on the results of the research and analysis carried out that criminal liability of court handed over the child is considered ineffective, because the modern punishment system does not apply torture to children but more attention to the best interests for children.